Word processing - Hollerbach, Lew (Hong Kong : Pitman, 1983)
The author discusses the word "word processor" and try to explain it in different facet that covers both the kinds of machine: the dedicated word processor used only for word processing, and a general-purpose personal computer used for word processing other uses.
Includes bibliographical references
hza 29/01/2019
Loans
Keywords: word processing; Equipment and supplies